EVALUASI PENGGUNAAN MANUAL DAN AUTOMATED SOFTWARE TESTING PADA PELAKSANAAN END-TO-END TESTING - Joan Lian Min; Adila Istiqomah; Ani Rahmani (P3M Politeknik Negeri Indramayu, 2020)
In software development life cycle, testing is needed to ensure the quality of the software before it is released. Choosing the testing technique depends on the characteristics of the software to be released. Web-based applications, for example, will tend to use end-to-end testing techniques to ensure web pages interact according to requirements. The cycle of software development recently is getting shorter. It is necessary to study to determine the testing implementation techniques (manually or automated) on the right end-to-end testing. The research objective is to look at the characteristics and technical testing of end-to-end testing that can be done in software development, both manually and automatically. The result showed that the number of iterations of end-to-end testing is very influential in the selection of quality techniques used. That can be a basis for determining testing techniques: manual or automatic.